PTU-152 Pepsin In Saliva For The Diagnosis Of Gastro-esophageal Reflux Disease. (9th June 2014) - Hayat, JO; Gabieta-Somnez, S; Yazaki, E; Kang, J-Y; Woodcock, A; Dettmar, P; Mabary, J; Knowles, C; Sifrim, D
Abstract : Introduction: Current diagnostic tests for GORD have moderate sensitivity/specificity and can be invasive and expensive. Pepsin detection in saliva has been proposed as an "office-based" method for GORD diagnosis. The aims of this study were to establish normal values of salivary pepsin in a large cohort of healthy asymptomatic subjects and to determine its value to discriminate patients with reflux-related symptoms (GORD, hypersensitive oesophagus) from functional heartburn. Methods: 100 asymptomatic controls and 111 patients with heartburn underwent MII-pH monitoring and simultaneous salivary pepsin determination on waking, after lunch and dinner. Cut off value for pepsin positivity was 16 ng/ml. Patients were divided into GORD (increased acid exposure time (AET) n = 58); Hypersensitive Oesophagus (HO) (normal AET and + SAP), n = 26) and Functional Heartburn (FH) (normal AET and – SAP, n = 27). Multiple group comparisons were performed using one-way ANOVA followed by with Tukey's Test for Gaussian distributed data and the Kruskall-Wallis Test with Dunns comparison for non-Gaussian data. Receiver Operator Characteristic curves were constructed to determine and compare the sensitivity and specificity of different pepsin cut-off concentrations. Results: 1/3 of asymptomatic subjects had pepsin in saliva at low concentration (0(0–59) ng/ml). Patients with reflux-related symptoms (GORD and HO) had higher prevalence (77–89%) and pepsin concentration than controls (HO, 237(52–311) ng/ml and GORD, 121(29–252) ng/ml) (p < 0.05). Patients with FH had low prevalence (33%) and concentration of pepsin in saliva (0(0–40) ng/ml). The area under the receiver operating characteristic curve had a value of 0.8034 +/-0.04 (95% confidence interval 0.719 to 0.8873, p < 0.0001). A positive test had 77.6% sensitivity and 63.2% specificity for diagnosis of GORD/HO. When all saliva samples were negative, there was 80% probability that symptoms were not due to reflux (FH). One positive sample with >210 ng/ml pepsin suggested the presence of GORD/HO with 95% probability. Conclusion: In patients with symptoms suggestive of GORD, salivary pepsin can be used to confirm or reject the diagnosis before empirical PPI treatment. This may lessen the use of unnecessary anti-reflux therapy and the need for further invasive and expensive diagnostic methods. Disclosure of Interest: J. Hayat: None Declared, S. Gabieta-Somnez: None Declared, E. Yazaki: None Declared, J.-Y. Kang: None Declared, A. Woodcock Employee of: RD Biomed Ltd, P. Dettmar Employee of: RD Biomed Ltd, J. Mabary Employee of: Sandhill Sci., C. Knowles: None Declared, D. Sifrim Grant/research support from: Sandhill Sci.